Netrin‐1 and B‐cell maturation antigen expression in a large cohort of 361 lymphomas: sensitive and specific staining in plasmablastic lymphomas, and therapeutic perspectives - Marie Donzel; Alexis Trecourt; Hervé Ghesquières; Thi‐Thuy‐Trinh Nguyen; Sara Dandash; Morgane Denis; Emeline Cros‐Perrial; Juliette Fontaine; Charles Dumontet; Alexandra Traverse‐Glehen (The Journal of Pathology: Clinical Research)
Abstract Netrin‐1 and B‐cell maturation antigen (BCMA) are currently being evaluated as therapeutic targets in oncology. However, studies investigating their expression in mature human lymphoid malignancies are sparse. This study aimed to investigate the expression of BCMA and Netrin‐1 in a large cohort of lymphomas to determine their potential role as biomarkers or therapeutic targets. BCMA and Netrin‐1 expression was investigated comprehensively using immunohistochemistry in a cohort that included 261 B‐cell lymphomas, 45 T‐cell lymphomas, and 55 classical Hodgkin lymphomas. Netrin‐1 displayed a cytoplasmic staining pattern in plasmablastic lymphomas (27/28, 96%) and classical Hodgkin lymphomas (8/55, 15%). BCMA displayed cytoplasmic staining in most plasmablastic lymphomas (17/20, 85%). Among mature B‐cell lymphomas, Netrin‐1 and BCMA displayed sensitive (96% and 85%, respectively) and specific (100% and 95%, respectively) staining in plasmablastic lymphomas. These results suggest that these proteins may help pathologists in complex diagnoses and reinforce the interest in developing clinical trials assessing Netrin‐1 or BCMA‐targeted therapies in plasmablastic lymphoma and classical Hodgkin lymphomas, for which our therapeutic arsenal is weak.